#TITLE_ALTERNATIVE# - (NIM 12205040); Pembimbing: Ir. Tutuka Ariadji, M.Sc., Ph.D., SOBANI
There are two important parameters in naturally fractured reservoirs which are very important in predicting the reservoir performance, i.e, storativity ratio and interporosity flow coefficients. This paper explains about a relationship between storativity ratio and recovery factor at plateau rate period, and an optimization to get an optimum oil rate. This study involves several PVT analysis, pressure transient analysis, and nodal system analysis. A reservoir model was constructed to predict the reservoir performance. Furthermore, a sensitivity analysis was conducted in this study to investigate the reservoir performance by changing value of storativity ratio and interporosity flow coefficients. The results of the sensitivity analysis show that the higher storativity ratio generates higher the recovery factor at plateau rate period, while changing in interporosity flow coefficient doesnÃ‚Â’t give a significant change in the recovery factor. Therefore, a recovery factor equation at plateau rate period as a function of storativity ratio has been created. Furthermore, an optimization analysis by doing Gas Oil Ratio (GOR) sensitivity gives result of an optimum oil rate at a GOR, value that is 2050 STB/day at GOR of 2600 scf/stb.